A Uniform Description of Perioperative Brain MRI Findings in Infants with Severe Congenital Heart Disease: Results of a European Collaboration - Stegeman, R.; Feldmann, M.; Claessens, N.H.P.; Jansen, N.J.G.; Breur, J.M.P.J.; de Vries, L.S.; Logeswaran, T.; Reich, B.; Knirsch, W.; Kottke, R.; Hagmann, C.; Latal, B.; et al. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: A uniform description of brain MR imaging findings in infants with severe congenital heart disease to assess risk factors, predict outcome, and compare centers is lacking. Our objective was to uniformly describe the spectrum of perioperative brain MR imaging findings in infants with congenital heart disease.MATERIALS AND METHODS: Prospective observational studies were performed at 3 European centers between 2009 and 2019. Brain MR imaging was performed preoperatively and/or postoperatively in infants with transposition of the great arteries, single-ventricle physiology, or left ventricular outflow tract obstruction undergoing cardiac surgery within the first 6 weeks of life. Brain injury was assessed on T1, T2, DWI, SWI, and MRV. A subsample of images was assessed jointly to reach a consensus.RESULTS: A total of 348 MR imaging scans (180 preoperatively, 168 postoperatively, 146 pre- and postoperatively) were obtained in 202 infants. Preoperative, new postoperative, and cumulative postoperative white matter injury was identified in 25%, 30%, and 36%; arterial ischemic stroke, in 6%, 10%, and 14%; hypoxic-ischemic watershed injury in 2%, 1%, and 1%; intraparenchymal cerebral hemorrhage, in 0%, 4%, and 5%; cerebellar hemorrhage, in 6%, 2%, and 6%; intraventricular hemorrhage, in 14%, 6%, and 13%; subdural hemorrhage, in 29%, 17%, and 29%; and cerebral sinovenous thrombosis, in 0%, 10%, and 10%, respectively.CONCLUSIONS: A broad spectrum of perioperative brain MR imaging findings was found in infants with severe congenital heart disease. We propose an MR imaging protocol including T1-, T2-, diffusion-, and susceptibility-weighted imaging, and MRV to identify ischemic, hemorrhagic, and thrombotic lesions observed in this patient group.AISarterial ischemic strokeCHDsevere congenital heart diseaseCSVTcerebral sinovenous thrombosisIVHintraventricular hemorrhageKCLSt. Thomas’ Hospital LondonLVOTOleft ventricular outflow tract obstructionSVPsingle ventricle physiologyTGAtransposition of the great arteriesUCZUniversity Children’s Hospital ZurichWKZWilhelmina Children’s Hospital UtrechtWMIwhite matter injury